Genomic epidemiology of SARS-CoV-2 in Cambodia, January 2020 to February 2021. Issue 1 (16th December 2022) - Su, Yvonne C F; Ma, Jordan Z J; Ou, Tey Putita; Pum, Leakhena; Krang, Sidonn; Raftery, Philomena; Kinzer, Michael H; Bohl, Jennifer; Ieng, Vanra; Kab, Vannda; Patel, Sarika; Sar, Borann; et al.
Abstract: The first case of coronavirus disease 2019 (COVID-19) in Cambodia was confirmed on 27 January 2020 in a traveller from Wuhan. Cambodia subsequently implemented strict travel restrictions, and although intermittent cases were reported during the first year of the COVID-19 pandemic, no apparent widespread community transmission was detected. Investigating the routes of severe acute respiratory coronavirus 2 (SARS-CoV-2) introduction into the country was critical for evaluating the implementation of public health interventions and assessing the effectiveness of social control measures. Genomic sequencing technologies have enabled rapid detection and monitoring of emerging variants of SARS-CoV-2. Here, we detected 478 confirmed COVID-19 cases in Cambodia between 27 January 2020 and 14 February 2021, 81.3 per cent in imported cases. Among them, fifty-four SARS-CoV-2 genomes were sequenced and analysed along with representative global lineages. Despite the low number of confirmed cases, we found a high diversity of Cambodian viruses that belonged to at least seventeen distinct PANGO lineages. Phylogenetic inference of SARS-CoV-2 revealed that the genetic diversity of Cambodian viruses resulted from multiple independent introductions from diverse regions, predominantly, Eastern Asia, Europe, and Southeast Asia. Most cases were quickly isolated, limiting community spread, although there was an A.23.1 variant cluster in Phnom Penh in November 2020 that resulted in a small-scale local transmission. The overall low incidence of COVID-19 infections suggests that Cambodia's early containment strategies, including travel restrictions, aggressive testing and strict quarantine measures, were effective in preventing large community outbreaks of COVID-19.